Validation of a parent-proxy, obesity-specific Health-Related Quality of Life measure - sizing them up - in Singaporean adolescents seeking obesity treatment - Wang Chin Eileen Ng; Khairunisa Binte Khaider; Qiao Fan; Chu Shan Elaine Chew (Proceedings of Singapore Healthcare)
Background Condition-specific measures of Health-Related Quality of Life (HRQoL) are more sensitive than generic tools. Sizing Them Up (STU) is a parent-proxy, obesity-specific HRQoL measure which was found to be reliable and valid internationally, but has yet to be utilised in Singapore. Objectives Our study aims to i) validate STU in adolescents seeking obesity therapy in KK Women’s and Children’s Hospital (KKH); and ii) determine demographic factors associated with STU scores. Methods We recruited 91 adolescents aged between 11 and 17 years old and their parents from KKH between June 2022 and January 2023. Parents completed STU and the generic Pediatric Quality of Life Inventory (PedsQL) upon recruitment, and repeated STU at least 2 weeks later. Results 65% of participants were males, with a mean Body Mass Index (BMI) of 32.3 ± 5.1 kg/m 2 and mean age of 13.6 ± 1.8 years old. STU demonstrated strong internal consistency (overall Cronbach’s α = 0.85) and moderate test-retest reliability (intraclass correlation coefficients = 0.30-0.70). There was high correlation between STU scores and i) the adolescents’ BMI; and ii) equivalent domains of PedsQL, suggesting moderate to strong construct and convergent validity respectively. Indian adolescents, lower parental education level and single parents were associated with poorer STU scores. Conclusion STU is a reliable, valid obesity-specific HRQoL measure in a local clinical population of adolescents undergoing obesity therapy, and can help clinicians to understand parents’ impression of the impact of obesity on their child. Knowing the demographic variables associated with STU can enable clinicians to identify adolescents whose HRQoL are disproportionately affected by obesity.